Multifaceted and Age-Dependent Phenotypes Associated With Biallelic PNPLA6 Gene Variants: Eight Novel Cases and Review of the Literature - Nanetti, Lorenzo; Di Bella, Daniela; Magri, Stefania; Fichera, Mario; Sarto, Elisa; Castaldo, Anna; Mongelli, Alessia; Baratta, Silvia; Fenu, Silvia; Moscatelli, Marco; Bonati, Maria Teresa; Martinuzzi, Andrea; et al. (Frontiers in Neurology, 2022)
A wide spectrum of neurodegenerative diseases has been associated with PNPLA6 (patatin-like phospholipase domain-containing protein 6) gene mutations, including spastic paraplegia type 39, Gordon-Holmes, Boucher-Neuhauser, Oliver-Mc Farlane and Laurence-Moon syndromes. These syndromes present variable and overlapping clinical symptoms, encompassing cerebellar ataxia, hypogonadotropic hypogonadism, chorioretinal dystrophy, spastic paraplegia, muscle wasting, peripheral neuropathy and cognitive impairment. In the present study, we performed a wide genetic screening in 292 patients presenting with ataxia or spastic paraplegia using a probe-based customize gene panel covering >200 genes associated with spinocerebellar diseases. We identified 6 novel and 4 recurrent PNPLA6 gene variants in eight patients (2.7%). Six patients presented an infantile or juvenile onset (age <18), and 2 patients had an adult onset. Cerebellar ataxia was observed in seven patients and spastic paraplegia in one patient. Progression of cerebellar symptoms was slow in all patients, who retained ambulation even after a mean disease duration of 15 years. Brain MRI showed cerebellar atrophy in 6/8 patients, more pronounced in superior and dorsal vermis lobules (I to VII). Additional clinical features included hypogonadotropic hypogonadism (5/8), growth hormone deficiency (2/8), peripheral axonal neuropathy (4/8), cognitive impairment (3/8), chorioretinal dystrophy (2/8), and bilateral vestibular areflexia with reduced visual vestibule-ocular reflex (1/8). In accordance with previous studies, chorioretinal dystrophy was the most frequent presenting symptoms in early onset patients, hypogonadotropic hypogonadism in juvenile onset cases, and cerebellar ataxia in adult patients. One patient had an initial clinical presentation compatible with Cerebellar Ataxia with Neuropathy and Vestibular Areflexia Syndrome (CANVAS), but no pathological expansions in the RFC1 gene. In conclusion, PNPLA6 patients present a variable age of onset spanning from infancy to adulthood, and each clinical symptom has an age-dependent manifestation thus requiring a multi-systemic diagnostic approach. The description of patients presenting very late-onset cerebellar ataxia suggests that PNPLA genetic screening should also be considered in the diagnostic work-out of adult cerebellar ataxia.